2013
DOI: 10.1051/0004-6361/201322240
|View full text |Cite
|
Sign up to set email alerts
|

New and updated stellar parameters for 90 transit hosts

Abstract: Context. Precise stellar parameters are crucial in exoplanet research for correctly determining the planetary parameters. For stars hosting a transiting planet, determining the planetary mass and radius depends on the stellar mass and radius, which in turn depend on the atmospheric stellar parameters. Different methods can provide different results, which leads to different planet characteristics. Aims. In this paper, we use a uniform method to spectroscopically derive stellar atmospheric parameters, chemical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
112
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(128 citation statements)
references
References 83 publications
(50 reference statements)
15
112
1
Order By: Relevance
“…These computations are based on equivalent widths of iron lines. Unlike other works, the computations based on specific line list of Sousa et al (2008) show little dependence between surface gravities and effective temperature (Mortier et al 2013b). A similar behaviour was also shown in the paper from Torres et al (2012) for a similar procedure also based on equivalent widths.…”
Section: O B S E Rvat I O Na L Data a N D M E T H O D O L O G Ysupporting
confidence: 81%
See 2 more Smart Citations
“…These computations are based on equivalent widths of iron lines. Unlike other works, the computations based on specific line list of Sousa et al (2008) show little dependence between surface gravities and effective temperature (Mortier et al 2013b). A similar behaviour was also shown in the paper from Torres et al (2012) for a similar procedure also based on equivalent widths.…”
Section: O B S E Rvat I O Na L Data a N D M E T H O D O L O G Ysupporting
confidence: 81%
“…This analysis only evaluates the individual impact that these parameters have on the mass determination. Correlations between the effective temperature and surface gravity uncertainties were disregarded since the computations based on the specific line list of Sousa et al (2008) show little dependence on surface gravities and effective temperature (Mortier et al 2013b). In this way, we observed that the fraction of stars in the sample which suffer a significant mass shift when this procedure is applied is largest for the spectroscopic approach.…”
Section: R E S U Lt S a N D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stellar atmospheric parameters were taken from Sousa et al (2008Sousa et al ( , 2011a for HARPS stars and from Santos et al (2004Santos et al ( , 2005, Sousa et al (2006) and Mortier et al (2013) for the rest of the planet hosts. The errors of the parameters from Santos et al (2004Santos et al ( , 2005 are of the order of 44 K for T eff , 0.11 dex for log g, 0.08 km s −1 for ξ t , 0.06 dex for metallicity and 0.05 M for the masses.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore do not expect surface gravity to introduce significant effects on the computation of individual chemical abundances from non-ionised species. In this line, Mortier et al (2013) computed chemical abundances of 90 stars with transiting exoplanets using spectroscopic log g values and log g estimates derived using the stellar density determined from the light curve. They found that only the abundances from ionised species are significantly affected.…”
Section: Photometric Parameters and Comparison With Previous Workmentioning
confidence: 99%